Applying an intraoperative predictive indicator for postoperative pancreatic fistula: randomized preclinical trial - Pausch, Thomas; Mitzscherling, Clara; Aubert, Ophelia; Liu, Xinchun; Gesslein, Bodil; Bruckner, Thomas; Kommoss, Felix; Golriz, Mohammad; Mehrabi, Arianeb; Hackert, Thilo (The British journal of surgery, 2021)
Leaking pancreatic fluid can contribute to postoperative pancreatic fistula (POPF), which can complicate pancreatic surgery. Surgeons lack reliable tools to ide